ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGABDOPSIAN E-COMMERCE DI KELURAHAN CEPOGO BOYOLALI - Prasetya, Adhitya Yoga (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
E-commerce has been giving a lot of benefits to small and medium enterprises (SMEs), but there are only a few SMEs which have adopted it. Therefore, it is necessary to find out what are the factors that support SMEs to adopt E-commerce. So far, researches on E-commerce have been done on foreign-large-scale businesses, while researches on SMEs especially about the adoption of E-commerce have been a few. That is why this research will discuss the adoption of E-commerce on Indonesian SMEs and will include the factors that support E-commerce adoption. The problems in this research are elaborated into research questions, i.e. do, top management support, organizational readiness, external pressure, and perceived benefits have significant positive effect to E-commerce adoption? And does the adoption have significant positive effect to companyâs performance? The purpose of this research is to analyze factors that support E-commerce adoption on Indonesian SMEs and to analyze whether the adoption improves the performance of the SMEs. This technique is chosen because it is the second generation of multivariate analyzing technique that enables researchers to test the relation between complex variables to get an overall view of the whole model. Besides, SEM can also test a series of a complicated relation simultaneously. The results of this research explain that top management support, organizational readiness, external pressure, and perceived benefits have Significant positive effect to E-commerce adoption, and the adoption have significant positive effect to companyâs performance.